2021
DOI: 10.24875/bmhim.20000399
|View full text |Cite
|
Sign up to set email alerts
|

Fórmulas metabólicas disponibles en México para pacientes con fenilcetonuria

Abstract: La fenilcetonuria y otras hiperfenilalaninemias son enfermedades genéticas cuya detección actualmente es obligatoria en México, tanto en el sector público como en el privado. La detección y el tratamiento oportunos han demostrado prevenir las manifestaciones neurológicas y la discapacidad que caracterizan esta enfermedad. Por ello, es de suma importancia que el pediatra y el personal de salud involucrados en la atención de estos pacientes conozcan, comprendan e implementen el manejo nutricional de manera corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In these studies, it is suggested that, in children experiencing faltering growth, it is necessary to increase energy, protein and micronutrients [ 55 ]. An accurate estimation of the protein requirement from metabolic formula in HPA/PKU patients is especially important in low- and middle-income countries, in which Phe-free metabolic formula is scarce and costly [ 51 , 56 ]. Recommending an unnecessarily high P:E ratio may contradict PKU recommendation guidelines and require excessive and expensive protein substitutes, including metabolic formula [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, it is suggested that, in children experiencing faltering growth, it is necessary to increase energy, protein and micronutrients [ 55 ]. An accurate estimation of the protein requirement from metabolic formula in HPA/PKU patients is especially important in low- and middle-income countries, in which Phe-free metabolic formula is scarce and costly [ 51 , 56 ]. Recommending an unnecessarily high P:E ratio may contradict PKU recommendation guidelines and require excessive and expensive protein substitutes, including metabolic formula [ 57 ].…”
Section: Discussionmentioning
confidence: 99%